Islamic Thought in the Era of Khulafa al-Rasyidin: A Literature Review - Umar, Hendra; Indo Santalia (HM Publisher, 2022)
In the periodization of the history of Islamic thought, the era of the Companions is categorized as the era of Khulafā al-Rāsyidīn, which lasted approximately 30 years, namely since the death of the Prophet Muhammad and the appointment of Abū Bakr al-Ṣiddiq ra. as caliph (11 H/632 AD) until the death of Caliph Alī bin Abī Ṭālib ra. (41 H/661 AD). Even after that time, there were still many friends who were still alive, the period after that was categorized as the era of the Islamic empire led by various dynasties. The division of the period of Islamic thought certainly uses a political approach. This approach is not without reason because it will be seen that government politics has a lot of influence on the development of Islamic thought. This literature review aims to describe the socio-cultural background and development of Islamic thought in the era of the companions of the Prophet Muhammad.